2015
DOI: 10.1002/jbmr.2730
|View full text |Cite
|
Sign up to set email alerts
|

Calcaneal Quantitative Ultrasound Indicates Reduced Bone Status Among Physically Active Adult Forager-Horticulturalists

Abstract: Sedentary lifestyle contributes to osteoporosis and fragility fracture risks among modern humans, but whether such risks are prevalent in physically active pre-industrial societies with lower life expectancies is unclear. Osteoporosis should be readily observable in pre-industrial societies if it was regularly experienced over human history. In this study of 142 older adult Tsimane forager-horticulturalists (mean age±SD=62.1±8.6, range=50-85, 51% female) we use calcaneal quantitative ultrasonography (qUS) to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 75 publications
(169 reference statements)
1
39
0
Order By: Relevance
“…On the one hand, a clinical model might argue that any growth deficit relative to standards is evidence of suffering, and a failure of a child to “adapt” to disease. On the other, an adaptationist perspective might suggest that small stature can be adaptive due to reduced energy demands, improved thermoregulation, or faster maturation (Stinson, 1990; Walker et al, 2006; Migliano et al, 2007), or that overall smaller stature in Amazonians may represent an adaptation to high pathogen load, and the need to prioritize energy for immune defenses (Blackwell et al, 2016; Gurven et al, 2016b; Stieglitz et al, 2016; Urlacher et al, 2016a)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, a clinical model might argue that any growth deficit relative to standards is evidence of suffering, and a failure of a child to “adapt” to disease. On the other, an adaptationist perspective might suggest that small stature can be adaptive due to reduced energy demands, improved thermoregulation, or faster maturation (Stinson, 1990; Walker et al, 2006; Migliano et al, 2007), or that overall smaller stature in Amazonians may represent an adaptation to high pathogen load, and the need to prioritize energy for immune defenses (Blackwell et al, 2016; Gurven et al, 2016b; Stieglitz et al, 2016; Urlacher et al, 2016a)…”
Section: Discussionmentioning
confidence: 99%
“…In general Tsimane children are short and lean, but have low rates of wasting and arm muscularity similar to US children, suggesting adequate protein (Foster et al, 2005). However, stunting is prevalent (Gurven, 2012), and low bone mineral density suggests the possibility of micronutrient deficiencies (Stieglitz, Beheim, Trumble, Madimenos, Kaplan, & Gurven, 2015;Stieglitz, Madimenos, Kaplan, & Gurven, 2016). Tsimane are a natural fertility population, with a total fertility rate of 9.1 births per woman (Blackwell, Tamayo, Beheim, Trumble, Stieglitz et al, 2015;Gurven, Kaplan, & Supa, 2007; McAllister, ; women breastfeed their infants on-demand, weaning at 19 months on average (Veile et al, 2014).…”
Section: The Tsimanementioning
confidence: 99%
“…Whether low bone mass is prevalent in physically active pre‐industrial populations with lower life expectancies and greater nutritional stress, pathogen burden and fertility is an open question. Several recent studies of Tsimane forager‐horticulturalists of lowland Bolivia, the population studied here, found reduced indices of calcaneal stiffness among Tsimane compared with more sedentary American matched controls, and more rapid age‐related stiffness decline among older adult Tsimane compared with Americans, Chinese, Dutch, and Germans (Stieglitz, Beheim, Trumble, Madimenos, Kaplan, & Gurven, ; Stieglitz, Madimenos, Kaplan, & Gurven, ). Relatedly, analysis of skeletal remains reveals that Australian hunter‐gatherers exhibit reduced limb cortical area compared with more sedentary populations (i.e., Khoi‐San, Zulu, African American; Carlson, Grine, & Pearson, ), indicating that increased postcranial thickness is not a hallmark of hunter‐gatherers.…”
Section: Introductionmentioning
confidence: 57%
“…Women's SOS undergoes accelerated declines around the age at menopause, presumably due to associated changes in mineral regulating hormones (e.g., estrogen, progesterone). Steeper age‐related declines in women's bone strength appears to be a species‐typical pattern (Khosla, ; Stieglitz et al, ), although whether women in contemporary pre‐industrial populations present different cross‐sectional bone geometric properties and increased fragility fracture risk remains unexplored. Consistent with P1 we found that women's radial SOS declines by 0.56 SDs/decade (2.5%), which is greater than their tibial SOS decline of 0.25 SDs/decade (0.9%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation